Dystopias of modernity. An approximation to the political function of the dystopian narrative (ALPHA. Journal of Arts, Literature and Philosophy, 2022)
This article aims to delve into the political function of the dystopian narrative, understood as a type of political image. Following of Gordin, Tilley & Prakash´s (2010) intuition, that dystopias are utopias that have gone wrong, it suggests that the dystopian narrative seeks to build an undesirable political image that permits the breaking away from the capture of desire produced by the pursuit of a certain utopia-illusion. We propose, as a key to the reading of dystopian narratives, that their emergence and proliferation stems from the historical experiences that account for the failure of the emancipatory impetus of modernity and its drift into social and political systems that perfect domination. Specifically, in the terms of Wallerstein (1995), the process by which the modernity of technology is historically imposed on the modernity of liberation.
Keywords: Dystopian narratives; Utopias; Enlightenment; Modernity of technology; Modernity of liberation.